2014
DOI: 10.1002/nbm.3230
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of SNR and parallel imaging improvements using composite arrays

Abstract: Composite MRI arrays consist of triplets where two orthogonal upright loops are placed over the same imaging area as a standard surface coil. The optimal height of the upright coils is approximately half the width for the 7 cm coils used in this work. Resistive and magnetic coupling is shown to be negligible within each coil triplet. Experimental evaluation of imaging performance was carried out on a Philips 3 T Achieva scanner using an eight-coil composite array consisting of three surface coils and five upri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Thus, simulations seem to overestimate the central SNR of the dipole array relative to that of the vertical loops array. This most likely reflects the fact that SNR of an array depends not only on B1- profile of individual elements, but also on coupling between them and, very important, on the hardware connecting the element and preamplifier . Figure D shows the ratio of the SNR maps of the 16‐element dipole array to that of the array of 8 surface loops only.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, simulations seem to overestimate the central SNR of the dipole array relative to that of the vertical loops array. This most likely reflects the fact that SNR of an array depends not only on B1- profile of individual elements, but also on coupling between them and, very important, on the hardware connecting the element and preamplifier . Figure D shows the ratio of the SNR maps of the 16‐element dipole array to that of the array of 8 surface loops only.…”
Section: Resultsmentioning
confidence: 99%
“…Another study, which may shed light on the problem of central SNR improvement, also deals with a spherical phantom and arrays, which consist of circular surface loops and so‐called composite elements . Each composite element contains a surface loop and 2 orthogonal “vertical” loops, positioned perpendicularly to both the surface loop and each other.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the authors demonstrated that the composite array slightly improves SNR near the center of the spherical phantom compared to an array of surface coils with the same total number of loops (both surface and vertical). Interestingly, the SNR enhancement was substantially greater (up to ~30% for 56‐element arrays) when noise from both the matching networks and preamplifiers was taken into account . Therefore, not only the realistic voxel model and array holder, but also realistic schematics of matching networks and preamplifiers may need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various coil types provide these patterns, including upright coils [5]. Composite coils are the combination of a surface coil and two orthogonal upright coils into a triplet [6], [7]. They have been shown to better approximate the electromagnetic fields required to approach the uSNRJ3] [5].…”
Section: Introductionmentioning
confidence: 99%